The San Juan Municipal Library a proposal - Alejandro, Reynaldo G.; Mangahas, Ruby K. (Quezon City : Institute of Library Science, University of the Philippines, 1966)
Discusses the organization and administration of the proposed municipal library of San Juan. It likewise includes a five year development plan for the proposed library.
Vita.
Special Problem (Master of Library Science)--University of the Philippines Diliman
Keywords: Municipal reference libraries -- San Juan (Rizal).